HUBUNGAN OPTIMISME TEHADAP RESILIENSI PADA MAHASISWA TINGKAT AKHIR YANG MENGERJAKAN SKRIPSI - Umroh, Niajeng Ma'rifatul; Al Musafiri, M Rizqon (Jurnal At-Taujih, 2022)
Various challenges and difficulties caused by writing a thesis are problems that cannot be avoided for every final year student. They are required to complete the thesis on time, even though there are many problems. Therefore, final year students working on theses need the role of resilience. Previous research has shown that resilience can be influenced by internal protective factors, one of which is optimism. This research uses correlational quantitative. Correlational research is research conducted to determine the relationship between two or more variables. The result of the calculation of the normality test is 0.528 which is greater than 0.05. So in accordance with the basis of decision making shows the data is normally distributed. The results of the correlation calculation also show 0.616 because it is close to 1, the relationship between optimism and resilience is strong, the results shown are positive. Value of Sig. 0.000> 0.05 then it can be concluded that there is a significant relationship. This indicates that if Optimism is high, Resilience is high and vice versa.